A NEEDS ASSESSMENT FOR A MANAGEMENT TRAINING PROGRAMME FOR STAFF OFFICERS AND AREA MANAGERS IN THE SOUTH AFRICAN NATIONAL DEFENCE FORCE (SANDF) SOCIAL WORK DIRECTORATE - Pitse, CA; Taute, FM (Social Work/Maatskaplike Werk, 2005)
Management is a process that requires both art and skill to be efficient and effective in service rendering. The goal of the study was to explore the need for a management training programme for staff officers and area managers in the SANDF Social Work Directorate in order to make recommendations for the development of a management training programme. This exploratory study utilised qualitative and quantitative methodology. No sampling was done as the entire population was used for the study. The staff officers and area managers in the nine provinces in South Africa, within the SANDF, Social Work Directorate, were used as the population in the study. The study clearly indicates that a formal management training programme is critical within the SANDF Social Work Directorate. It is recommended that a formal management training programme should be implemented within the SANDF Social Work Directorate to address the management needs identified in this empirical study. Various identified experts should be utilised in the provision of training.